A regional approach to drought index-insurance in Intergovernmental Authority on Development (IGAD) countries: Volume 1 Main report - Operational and technical feasibility assessment - Lung, Felix; Stutley, Charles; Kahiu, Njoki; Vrieling, Anton; Zewdie, Yihenew; Fava, Francesco P. (International Livestock Research Institute, 2021)
This study takes stock of over 10-years of experience and increasing coverage of index-based livestock insurance (IBLI) programs to protect pastoralists from drought shocks in the Intergovernmental Authority on Development (IGAD) region. The study reviews the status of national-level drought/climate risk financing solutions in the region and discusses the operational and technical feasibility of a regional IBLI program, summarizing critical lesson learned and providing a set of recommendations and options for regional implementation. The report has been prepared by the International Livestock Research Institute (ILRI) under the Drought Index-insurance for Resilience in the Sahel and Horn of Africa (DIRISHA) project supported by the UK Aid Science for Humanitarian Emergencies and Resilience (SHEAR) program. DIRISHA, the Swahili word for ‘window’, had the ambitious goal of advancing an evidence case to scale-up climate risk financing innovations that that seek to protect vulnerable dryland populations in the IGAD region and beyond in the face of climate shocks.